Investigating Translation Techniques through Theme-Rheme Analysis - Imaratul Ulwiyah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
ABSTRACT Translation is the process of transferring a message from one language to another with consideration to the equivalence. In the practice of translation, forms may change. The practice of translation should be done on the basis of linguistic theories as tools. Since the translator is concerned exclusively and continuously with meaning, it is not surprising that Halidayan linguistics which sees language primarily as a meaning potential should offer itself as a serviceable tool for determining the constituent part of a source language text network of relations with its translation. Therefore, this research will identify the translation technique through the information structure theories (Theme-Rheme) and its readability in BabyShark StoryBook Series. The method used in this study is qualitative descriptive. The data collection was conducted by using observation and note-taking techniques. Ten young children became target readers for the assessment to the readability of the translated text. The results show that the Theme-Rheme analysis can lead to find the translation techniques which were applied. They are Modulation, Transposition, Reduction and Amplification. The data reported here appear to support the assumption that the translator applied linguistic simplification and over explicitation in order to children fully grasp the text.Keywords:translation, theme-rheme, translation technique, readability